A new species of Memecylon (Melastomataceae) from the Western Ghats, India - Sivu, Ambikabai Raghavanpillai; Narayanan, Matalai Kokkaramath Ratheesh; Pradeep, Nediyaparambu Sukumaran; Kumar, Ettickal Sukumaran Santhosh; Pandurangan, Alagramam Govindasamy (Phytotaxa, 2014)
Memecylon ponmudianum, a new species of Melastomataceae from Thiruvananthapuram district, Kerala, India, is described and illustrated. The new species resembles M. terminale and M. subramanii but differs from the former by its larger and sessile leaves with cordate and amplexicaul leaf bases, robust and shortly peduncled inflorescences, pedicels distinctly shorter than the campanulate calyx, and from the latter by the terete stem and branchlets, smaller subsessile and amplexicaul leaves, terminal short peduncled umbellate cymes with terete peduncle and the pedicels distinctly shorter than calyx. A key to the Memecylon species with cordate leaf bases occurring in south India and Sri Lanka is also presented.